Investigating tangential access for location-based digital cultural heritage applications. Issue 122 (February 2019) - McGookin, David; Tahiroğlu, Koray; Vaittinen, Tuomas; Kytö, Mikko; Monastero, Beatrice; Carlos Vasquez, Juan
Abstract: As location-based digital cultural heritage applications are beginning to be applied outside 'traditional' cultural heritage sites, there is an increased need to consider their use amongst people who may be interested in the cultural heritage of a site, but have that interest as a tangential, opportunistic, aspect of their visit. We outline why this is important, and present issues in evaluating it. We then introduce Explore: a mobile, location-based, digital cultural heritage application for the Finnish recreational island of Seurasaari. By considering how the common visitor trajectory of a museum visit can be mapped onto a visit to the island, we were able to evaluate Explore with participants who were not primarily there to access cultural heritage. Evaluation with 45 participants over 5 days identified how the low immersion techniques used allowed participants to fit accessing cultural heritage around their visit, how participants managed group tension between those more and those less interested in Explore, as well as issues around considering the use of cultural heritage applications as a tangential purpose of a visit.